PERILAKU SINYAL AKUSTIK DAN VISUAL DARI KATAK JANTAN Staurois gutattus DI GUNUNG POTENG KALIMANTAN BARAT - Mohamad Jakaria; Junardi Junardi; Riyandi Riyandi (BERITA BIOLOGI, 2020)
The behavior of both acoustic and visual signals has been observed in Staurois gutattus black-spotted rock frogs. The aim of the study was to determine how S. gutattus frogs communicate to find their mates through acoustic and visual signals. This research was conducted in Mount Poteng, West Kalimantan. Data were analyzed descriptively and graphically to explain the relationship between the measured parameters. Data collection of advertisement call, foot-flagging and amplexus behavior is done directly in the field. All activities carried out are recorded with the camera. The duration of each part of the breeding activity is also calculated using a stopwatch. The male frog's advertisement call and foot-flagging are carried out by the male frogs while attracting their mates to mate. Where the foot-flagging activity was mostly carried out on the rock substrate (62%), while on the leaf substrate advertisement call was more dominant (47%). Then based on the duration, activity advertisement call, foot-flagging and amplexus the longest duration was performed by male frogs in the time range 18.00-05.59. Meanwhile, from the number of individuals, the advertisement call, foot-flagging and amplexus activities were mostly carried out at 18.00-05.59.